THE SEX AND AGE STRUCTURE OF THE CITIZEN POPULATION OF LIBYA, 1954 -64 - Srivastava, M. L. (Dirasat in Economics and Business, 1970)
The study of the composition of population in general and that of sex and age in particular has several advantages (Hawley, 1959). To begin with, for example, it provides an inventory of human resources available and permits the description of the population in a community. In these contexts it also permits the comparison between or among population groups. The study, in addition, serves as a guide to future changes in the structure of population in a community because these changes are heavily affected by the present size and composition of the population in that community. Further, the study provides the factors which are most important in analysing the components of population change, namely, fertility, mortality and migration. The study of sex and age composition in any population has an added advantage of providing indirect estimates of population change.